2017
DOI: 10.1016/j.pmedr.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Australian adults' behaviours, knowledge and perceptions of risk factors for heart disease: A cross-sectional study

Abstract: This research aimed to determine Australian adults' perceptions of risk factors for heart disease, self-reported behaviours relating to modifiable risk factors, and knowledge of leading causes of death. This study reports on HeartWatch survey data collected between January 2015 and December 2015 in a sample of Australian adults. The setting of the research was Australian communities, with all states and territories represented in the final sample. Participants were Australian adults aged 30–59 years (n = 8425)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Interestingly, even in those women with typical symptoms, there was a longer delay in seeking care and less concern for potential cardiac issues, in both the women themselves, and their health care providers [31]. The misperception that only men suffer heart attacks remains strong in our society leading women to under-estimate their risk [34]. Research has demonstrated that women are more likely to have lower socioeconomic status compared to men and this is associated with poorer MI awareness and emergency presentation [31].…”
Section: Presentation and Timingmentioning
confidence: 99%
“…Interestingly, even in those women with typical symptoms, there was a longer delay in seeking care and less concern for potential cardiac issues, in both the women themselves, and their health care providers [31]. The misperception that only men suffer heart attacks remains strong in our society leading women to under-estimate their risk [34]. Research has demonstrated that women are more likely to have lower socioeconomic status compared to men and this is associated with poorer MI awareness and emergency presentation [31].…”
Section: Presentation and Timingmentioning
confidence: 99%
“…A lack of knowledge of CV risk factors (CVRF) among women has been demonstrated by the majority of published studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The knowledge that CVD is the leading cause of death proved to be suboptimal among Australian and US women [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A lack of knowledge of CV risk factors (CVRF) among women has been demonstrated by the majority of published studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The knowledge that CVD is the leading cause of death proved to be suboptimal among Australian and US women [ 19 , 21 , 22 ]. A nationwide survey conducted by the Women’s Heart Alliance in 2014 to determine barriers and opportunities for women and physicians with regard to CVD showed that almost half of 1011 interviewed women did not recognize CVD as the number one killer of women in the US [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a national survey, 71% of the population with blood pressure levels ≥ 140/90 mmHg, our present threshold, were not aware they had hypertension 11 . We recently found that community awareness of high blood pressure as a forerunner of heart disease and stroke is very low in Australia 18 . Without better community awareness and engagement, we are unlikely to make progress.…”
mentioning
confidence: 99%